The Transformation of the Soviet Agriculture - Leonavičius, Vylius; Ozolinčiūtė, Eglė (Sociologija. Mintis ir veiksmas, 2019)
The Soviet past is crucial in understanding the processes of transformation of the Lithuanian kolkhoz system into the farming practices of free-market economy. The violent and forced incorporation of the nation-states into the Soviet Union radically transformed societies. In our analysis of kolkhoz system and its transformations, we use two different concepts – Soviet modernity and modernity of the Soviet period. These concepts let us to approach the agricultural project of the Soviet collective farming as an alternative system of social institutions for implementation of industrial farming of modern society. The concept of entangled modernity refers to interaction of two trends of modernization and defines the kolkhoz as a hybrid or a result of intertwining of two models of modernity – the universal and the Soviet one. By applying the concept of entangled modernity and hybrids to the interpretation of the kolkhoz’s post-Soviet transformation, the article explores the experiences of social actors and the inevitable human and material losses of the hybrid’s transformation. In our theoretical interpretation, we use data from interviews with former agents of the kolkhoz system and legislative documents.
Keywords: kolkhoz agriculture; hybrid modernity; postsoviet transition